East Java Left Behind: The Unspoken Crisis of Post-Covid Poverty - Hariz, Miftahul; Rasul D, Erwin Putra; Arsita K, Ni Made; Mahindah, Mahindah; Suparta, I Made (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The research outlines the impact of COVID-19 on poverty levels in East Java, Indonesia. Utilizing secondary information from BPS and governmental documents, the study reveals that poverty surged at the beginning of the pandemic due to increased living expenses and interruptions in economic operations. From 2022 to 2024, the poverty percentage steadily fell as a result of economic revival and social support. Poverty decreased from 10.38% in 2022 to 9.79% in 2024. Despite these improvements, issues such as inflation and digital disparities remain. The report advises enhancing social safety nets, accelerating digital development, boosting various economic sectors, and involving communities to maintain efforts in reducing poverty.